A Multiple Collision Channel Assignment Based on Imperfect Game Theory - Haofeng Dai; Shibiao He; Mian Tan; Pengyu Zheng; Hui Zhang (Dianxin kexue)
The channel allocation in wireless network will greatly affect the whole performance of the network. In order to solve this optimization problem, a kind of non cooperation channel allocation algorithm based on imperfect information was put forward. The network scene was assumed to be multihop Ad Hoc networks. So the multi-domain modeling conflict was more realistic. The algorithm constantly cyclically changed radio channel for each user to attempt to close to the Nash equilibrium point. The simulation results show that the algorithm can make the channel allocation strategy close to Nash equilibrium. At the same time, it can better maximize utilization.